1990
DOI: 10.1103/physrevb.41.9183
|View full text |Cite
|
Sign up to set email alerts
|

Series study of percolation moments in general dimension

Abstract: Series expansions for general moments of the bond-percolation cluster-size distribution on hypercubic lattices to 15th order in the concentration have been obtained. This is one more than the previously published series for the mean cluster size in three dimensions and four terms more for higher moments and higher dimensions. Critical exponents, amplitude ratios, and thresholds have been calculated from these and other series by a variety of independent analysis techniques. A comprehensive summary of extant es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
134
2
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 64 publications
23
134
2
2
Order By: Relevance
“…In [19], [20], it is argued that percolation in three dimensions can be viewed as a gauge theory and it can capsulate most of the features of confinement and the glueball spectrum. The values of the exponents γ and ν given at the end of the Section 4.2 are in a good agreement with the values of the corresponding exponenents of the 5-D percolation model which are: γ 5Dperc = 1.18 and ν 5Dperc = 0.57 (see [21]). Although this fact alone can not justify any further argumentation on a possible universality class issues, however it might be useful in providing a new point of view for the confinement mechanism along the extra dimension.…”
Section: Discussionsupporting
confidence: 78%
“…In [19], [20], it is argued that percolation in three dimensions can be viewed as a gauge theory and it can capsulate most of the features of confinement and the glueball spectrum. The values of the exponents γ and ν given at the end of the Section 4.2 are in a good agreement with the values of the corresponding exponenents of the 5-D percolation model which are: γ 5Dperc = 1.18 and ν 5Dperc = 0.57 (see [21]). Although this fact alone can not justify any further argumentation on a possible universality class issues, however it might be useful in providing a new point of view for the confinement mechanism along the extra dimension.…”
Section: Discussionsupporting
confidence: 78%
“…For the percolation systems η(d) has a weak minimum around d = 3 before becoming positive at d = 2. 57 The present results show that for the GG there is a deep minimum in η(d) near d = 4. This is in stark contrast to the situation in the canonical Ising, XY , or Heisenberg systems with no disorder where η(d) hardly changes at all when the degrees of freedom of the spin are modified.…”
Section: Discussionsupporting
confidence: 56%
“…These results are more precise than some of the published values for p c = 0.16005 ± 0.00015 [17], 0.1407 ± 0.0003 [18], and 0.11819 ± 0.00004 [17] for 4D bond, 5D site, and 5D bond percolation, respectively and for τ = 2.41 for 5D percolation; for 4D site percolation, Ballesteros et al [19] found the comparably precise value p c = 0.196901 ± 0.000005 (just slightly higher than ours) and τ = 2.3127 ± 0.0007. All simulation parameters and our results are summarized in Table I.…”
Section: Percolation Threshold and Fisher Exponentsupporting
confidence: 52%